(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
Nanosized sensor materials based on SnO2/Sb2O5 were obtained by a sol-gel method using ethyleneglycol and sensors on the base of these materials were created. Cerium additives of different concentrations were introduced to the gas sensitive layers the sensors to increase their sensitivities. Physico-chemical properties of the obtained nanomaterials were studied. Only reflexes which corresponds to tetragonal modification of SnO2 (cassiterite) were fixed by XRD method. It was established by TEM method that sizes of SnO2-Sb2O5 nanoparticles varied from 5 to 23 nm, and their average size was 12 nm. It was found that the most intense absorption bands at 537 cm-1 and 671 cm-1 in IR-spectrum correspond to vibrations of bonds between tin and oxygen in terminal Sn-O and bridging O-Sn-O fragment. DTA–DTG analysis of crystalline cerium chloride was carried out to optimize temperature regime of Ce-containing sensors sintering. It was found by DTA–DTG that crystallized water was removed stepwise that was accompanied by sequential formation of cerium hydrochlorides, oxychloride, and cerium oxide CeO2 during a process of CeCl3·7H2O heating..Gas sensitive properties of semiconductor sensors based on SnO2-Sb2O5 nanomaterial with different CeO2 contents were investigated. Study of sensors based on nanosized SnO2-Sb2O5 showed that the introduction of cerium additives leads to a significant increase in sensors’ sensitivity to 40 ppm hydrogen. Extremal dependence of the sensor sensitivity on the heater power consumption was established. Maximum of sensitivity corresponds to the sensor heater power consumption in the range of 0.35–0.4 W. The most sensitive sensors (γ=6.5) were prepared by impregnation of the nanosized SnO2-Sb2O5 material with solution of CeCl3 with a concentration 1.0·10-2 М. Extremal dependence of the sensors sensitivity on temperature was explained in terms of proceeding of heterogeneous catalytic H2 oxidation on the sensor gas-sensitive surface.